Transformational Leadership, Energizing Organizational Learning process, and Organizational Performance at Embroidery MSME in District Tasikmalaya - Muhammad Nurdin Yusuf; Aneu Yulianeu (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The article analyzed model of the impact of transformational leadership on the organizational learning process that energizes the organizational level, tested on 280 business owners and embroidery managers in Tasikmalaya. The researchers used quantitaive method. Questionnaires were sent to the owner and the manager of the Tasikmalaya Embroidery small-to medium-sized enterprises (MSME). The total 280 questionnaires were distributed with a return rate of 90%. There were 47 respondents with duplicate, incomplete, and invalid data because all answers were number 1, or respondents did not match the unit of analysis. The results showed that Transformational Leadership has an essential effect on the learning process in organizations in improving the performance of MSMEs. At the organizational level, the results of hierarchical linear modeling showed a positive relationship between transformational leadership and energizing organizational learning processes. At the organizational level, the regression analysis results showed that transformational leadership was positively related to an energizing organizational learning process, as measured by market-oriented criteria developed explicitly for the city and district of Tasikmalaya. Keywords: Transformational Leadership, Organizational Learning Process, Organizational Performance